Hydrodynamics of triangular-grid arrays of floating point-absorber wave energy converters with inter-body and bottom slack-mooring connections - Vicente, Pedro C. (2010)
It may be convenient that dense arrays of floating point absorbers are spread-moored to the sea bottom through only some of their elements (possibly located in the periphery), while the other array elements are prevented from drifting and colliding with each other by connections to adjacent elements. An array of identical floating point absorbers located at the grid points of an equilateral triangular grid is considered in the paper. A spread set of slack-mooring lines connect the peripheric floaters to the bottom. A weight is located at the centre of each triangle whose function is to pull the three floaters towards each other and keep the inter-body moorings lines under tension. The whole system – buoys, moorings and power take-off systems – is assumed linear, so that a frequency domain analysis may be employed. Equations are presented for a set of three identical point absorbers. This is then extended to more complex equilateral triangular grid arrays. Results from numerical simulations, with regular and irregular waves, are presented for the motions and power absorption of hemispherical converters in arrays of three and seven elements and different mooring and PTO parameters, and wave incidence angles. Comparisons are given with the unmoored and independently-moored buoy situations.